Effects of length and diameter of open-ended coaxial sensor on its reflection coefficient - You, Kok Yeow (2012)
This paper presents a calibration technique for a coaxial sensor using a transmission signal approach. The sensor was fabricated from commercially available RG402/U and RG405/U semi-rigid coaxial cable. The length of the coaxial sensor was correlated with the attenuation and standing wave inside the coaxial line. The functions of multiple reflection amplitude and tolerance length with respect to the actual length of coaxial line were empirically formulated using regression analysis. The tolerances and the undesired standing wave which occurs along the coaxial line were analyzed in detail.